2015
DOI: 10.1371/journal.pone.0132331
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Progressive Regional Brain Atrophy in CLN6 Batten Disease Affected Sheep Measured with Longitudinal Magnetic Resonance Imaging

Abstract: Variant late-infantile Batten disease is a neuronal ceroid lipofuscinosis caused by mutations in CLN6. It is a recessive genetic lysosomal storage disease characterised by progressive neurodegeneration. It starts insidiously and leads to blindness, epilepsy and dementia in affected children. Sheep that are homozygous for a natural mutation in CLN6 have an ovine form of Batten disease Here, we used in vivo magnetic resonance imaging to track brain changes in 4 unaffected carriers and 6 affected Batten disease s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
3
16
1
Order By: Relevance
“…3D). Features in this model recapitulate the gross anatomical findings in a naturally occurring ovine model caused by mutation of the CLN6 gene 21 .…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…3D). Features in this model recapitulate the gross anatomical findings in a naturally occurring ovine model caused by mutation of the CLN6 gene 21 .…”
Section: Resultssupporting
confidence: 57%
“…This time point was selected to provide the most animals in a specific 2 week period. In addition, this time point was similar to that used in another ovine study of naturally occurring CLN6 model (16 month) 21 .…”
Section: Methodsmentioning
confidence: 90%
“…Other common features of the ovine and human NCLs include progressive cerebral atrophy and enlargement of the cerebral ventricles (Frugier et al, 2008;Jolly et al, 2002Jolly et al, , 1989Woods et al, 1993). Neuroimaging techniques, such as magnetic resonance imaging (MRI) and computed tomography (CT), have been used to monitor changes of brain size and intracerebroventricular volumes in both human and ovine NCLs (Dyke et al, 2016;Jadav et al, 2014;Lobel et al, 2013;Sawiak et al, 2015;Valavanis, Friede, Schubinger, & Hayek, 1980;Woods et al, 1993). Viral-mediated gene therapy trials are being conducted in affected sheep (Palmer, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, studies have shown AD-associated neurofibrillary accumulation (tau pathology) in normal aged sheep (Braak et al, 1994, Nelson andSaper 1995); a feature which is absent in wild type rodents and has made AD modelling challenging in rats and mice (Hardy and Selkoe 2002). While the rate of naturally occurring dementia in sheep is unknown (as most farmed sheep are culled before reaching old age), sheep with cognitive deficits are studied due to natural mutations in genes causing Battens Disease in humans (Cook et al, 2002, Jolly et al, 1980, Weber and Pearce 2013 Sheep are readily trainable for use in tests of cognitive function (Morton and Avanzo 2011) and sheep suffering from a progressive neurological disease can be quantified longitudinally using modern methods, such as EEG (Perentos et al, 2015) and MRI (Sawiak et al, 2015).…”
Section: Introductionmentioning
confidence: 99%